Mechanical and physical characterizations of hydrothermally derived hydroxyapatite powder after being subjected to different holding time - Adnan, Noor Quratul Aine (2016)
aste cooking oils are problematic disposal especially in the developed countries. Options for disposing of waste cooking oil are limited. Therefore, in this research, vegetable waste cooking oil is used as raw material to produce renewable polymer foam as an alternative product. This is started with the crosslinking of renewable monomer with isocyanate to generated renewable polymer foam. Further process is comprised with the addition of synthetic epoxy or titanium dioxide (TiO2) by different ratio (wt/wt) of renewable monomer. Fabricated samples was divided into three types of foam namely as epoxy foam (EF), renewable polymer foam (RF) loaded with different percentage loading of titanium dioxide (TiO2) as filler namely as EF 1.3 and RF 1.3 and epoxy/renewable polymer foam (ERF). At prolonged UV irradiation exposure, the density of all specimens was increase but the pore sizes were decreased as the percentages of TiO2 were increased. For EF, RF and EFR samples shows highest at frequency absorption level (Hz) of a at each individual category with 0.965 at 2943 Hz, 0.995 at 3106 Hz, 0.945 at 3684 Hz. The lowest a at frequency absorption level (Hz) of EF, RF and ERF is 0.878 at 3181 Hz, 0.823 at 3184 Hz, 0.876 at 3526 Hz respectively. Meanwhile for composite samples EF1.3 and RF 1.3 shows higher a at absorption frequency level (Hz) of each individual category with 0.968 at 3928 Hz, 0.998 at 3728 Hz and lowest a at frequency absorption level (Hz) of 0.836 at 3512 Hz, 0.878 at 3915 Hz respectively. As a general remark, the highest loading of TiO2 show RF3 resulted in reduced of cell sizes after UV irradiation exposure and contributed the higher a. Thus, the morphological study of SEM was revealed that RF3 have smallest cell sizes after UV irradiation exposure with 681 µm diameter. In other words, the decrement in cell sizes of higher TiO2 loading was improved the sound absorption property at prolonged UV irradiation hours 1000 hours